STRATEGI PEMANFAATAN BUSSINESS CENTER SEBAGAI LABORATORIUM PEMBELAJARAN UNTUK MENINGKATKAN MINAT BERWIRAUSAHA DI SMKN 22 JAKARTA - Ratih Yuni Pratiwi; Widia Winata (PT. Hasba Edukasi Mandiri, 2025)
This study aims to describe the strategic utilization of the Business Center as a learning laboratory to enhance students' entrepreneurial interest at SMKN 22 Jakarta. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation involving the principal, entrepreneurship teachers, Business Center managers, entrepreneurship practitioners, and students. The data were analyzed thematically using data reduction, data display, and conclusion drawing.The findings indicate that the Business Center at SMKN 22 Jakarta has been strategically utilized as an entrepreneurial learning laboratory. The strategies implemented include: (1) project-based learning that enables students to design, produce, and market products directly; (2) intensive mentoring by teachers and business practitioners, providing students with real-world business insights and guidance; (3) student business expos that serve as platforms to showcase their products, build confidence, and foster entrepreneurial motivation; and (4) the development of a supportive entrepreneurial ecosystem through adequate facilities, curriculum integration, and collaboration with external partners.The utilization of the Business Center has proven effective in cultivating students' entrepreneurial attitudes, skills, and interests. Contextual learning based on real-life experience encourages students to be more prepared to face the challenges of the professional world and develop entrepreneurial potential from an early age.